Learning Polygons using English Language - Willyarto, Mario Nugroho (Bina Nusantara University, 2017)
The authors conducted a study related to using English in learning mathematics, for grade 7 junior high school students in a private national plus school. The purpose of this study was for the reader to open up further insights related to the topic. This study was carried out with experimental design, by doing different treatment between classes in the same level. The subjects of the study consisted of 63 students spread into three classes; 7A, 7B, and 7C. Class 7C was a control group, using Bahasa Indonesia (mother tongue) in learning Mathematics. Class 7A and 7B were the experimental groups, where 7A was in English and 7B used bilingual (English and Indonesian). Results of the study include the following; using English is not detrimental to the students in mark achievement that is shown by the average of the final mark of Mathematics that is not significantly different. The challenges that arise from learning Mathematics need to be reviewed from the process, readiness, independence, motivation of students and needs to be followed up critically so that students can achieve better results. Short and long-term programs need to be created and observed in order to support the learning process of Mathematics for students, such as training teachers to be able to teach mathematics in English, in supporting action study by teachers, managed by the school.